2008
DOI: 10.1161/circulationaha.107.741181
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle PET-CT Imaging of Macrophages in Inflammatory Atherosclerosis

Abstract: Background-Macrophages participate centrally in atherosclerosis, and macrophage markers (eg, CD68, correlate well with lesion severity and therapeutic modulation. On the basis of the avidity of lesional macrophages for polysaccharide-containing supramolecular structures such as nanoparticles, we have developed a new positron emission tomography (PET) agent with optimized pharmacokinetics to allow in vivo imaging at tracer concentrations. Methods and Results-A dextranated and DTPA-modified magnetofluorescent 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
389
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 523 publications
(401 citation statements)
references
References 33 publications
8
389
2
2
Order By: Relevance
“…Various imaging modalities have been used to study plaque formation and characteristics in the apoE−/− mouse model [9][10][11]. MRI has been used to study plaque burden in the abdominal aorta of mice [12][13][14][15], and recently, several studies have focused on pre-clinical evaluation of novel targeted contrast agents to identify molecular fingerprints of plaque vulnerability [7,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Various imaging modalities have been used to study plaque formation and characteristics in the apoE−/− mouse model [9][10][11]. MRI has been used to study plaque burden in the abdominal aorta of mice [12][13][14][15], and recently, several studies have focused on pre-clinical evaluation of novel targeted contrast agents to identify molecular fingerprints of plaque vulnerability [7,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Additional inaccuracies may arise when attempts are made to distinguish the negative contrast due to USPIO accumulation from that secondary to vessel calcification or inherent image artifacts, although positive contrast methods such as gradient echo acquisition for superparamagnetic particles/ susceptibility may help the image interpretation (26). In recent work (27), a radiotracer was bound to iron oxide nanoparticles to quantify the accumulation of these particles using PET. Indeed, Nahrendorf et al (27) demonstrated a strong correlation between the activity measured with PET and macrophage content in corresponding sections of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque macrophages are then imaged using a variety of techniques including micro-single-photon emission computed tomography (micro-SPECT), magnetic resonance imaging (MRI), and near infrared fluorescence (NIRF) microscopy. [82][83][84] NIRF microscopy has also been used to image proteolysis in the plaque by detecting the degradation of fluorescent substrates for the MMPs and cathepsins in atherosclerotic plaques in live mice. 85,86 Investigators have used these methods to study plaque growth in mice, and plaque regression after statin treatment.…”
Section: Leukocyte Collagen Receptorsmentioning
confidence: 99%